German industry and global enterprise : BASF : the history of a company - Abelshauser, Werner (Cambridge University Press, 2004)
This is a corporate history of BASF, which also explores the reasons for the extraordinary economic development of the German Empire, its role in supporting the German economy during two world wars, and its position in facilitating West Germany's quick return to the world market.